Effects Of Fermentation And Roasting Treatment On Fat Of Rambutan (Nephelium Lappaceum) Seed And Its Potential Utilization As Confectionery Fat - Febrianto, Noor Ariefandie (2013)
Rambutan (Nephelium lappaceum L.) is popular exotic fruit native to Malaysia and Indonesia which usually consumed fresh after harvested. Today, rambutan is already commercialized for the production of canned fruit, juice, jam, jellies, and marmalades. As the production of rambutan products increase, byproduct issues also become one of the problems that need to be solved. Rambutan seed is one of rambutan by-product that has a potential to be utilized, especially as rambutan seed fat (RSF). This research was carried out to study the prospect of fermentation and roasting pretreatment on rambutan seed to increase the value-added properties of rambutan seed fat. Rambutan seeds were fermented for 3, 6, 9, and 12 days and followed by roasting at 150˚C for 30 minutes. The extraction of RSF was carried out physically using a screw-press machine. Fermentation and/or roasting treatment carried out on rambutan seed significantly altered the physicochemical properties of rambutan seed fat. Fermentation not more than 9 days followed by the roasting process resulted in RSF with higher consistency, crystallization and melting points but lower thermal stability than unfermented RSF. The treatments also significantly increased the antioxidant activity of RSF. In addition, value-added properties such as desirable pyrazine flavor were also observed to be developed by the fermentation and roasting treatment. Six days of fermentation process followed by roasting has been observed to exhibit desirable characteristic of RSF.